The sustainability of health interventions implemented in Africa: an updated systematic review on evidence and future research perspectives - Ucheoma Nwaozuru; Patrick Murphy; Ashley Richard; Chisom Obiezu-Umeh; Thembekile Shato; Ifeoma Obionu; Titilola Gbajabiamila; David Oladele; Stacey Mason; Bryce P. Takenaka; Lateef Akeem Blessing; Alexis Engelhart; et al. (Implementation Science Communications)
Abstract Background Sustaining evidence-based interventions in resource-limited settings is critical to optimizing gains in health outcomes. In 2015, we published a review of the sustainability of health interventions in African countries, highlighting gaps in the measurement and conceptualization of sustainability in the region. This review updates and expands upon the original review to account for developments in the past decade and recommendations for promoting sustainability. Methods First, we searched five databases (PubMed, SCOPUS, Web of Science, Global Health, and Cumulated Index to Nursing and Allied Health Literature (CINAHL)) for studies published between 2015 and 2022. We repeated the search in 2023 and 2024. The review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. Studies were included if they reported on the sustainability of health interventions implemented in African countries. Study findings were summarized using descriptive statistics and narrative synthesis, and sustainability strategies were categorized based on the Expert Recommendations for Implementing Change (ERIC) strategies. Results Thirty-four publications with 22 distinct interventions were included in the review. Twelve African countries were represented in this review, with Nigeria (n = 6) having the most representation of available studies examining sustainability. Compared to the 2016 review, a similar proportion of studies clearly defined sustainability (52% in the current review versus 51% in the 2015 review). Eight unique strategies to foster sustainability emerged, namely: a) multi-sectorial partnership and developing stakeholder relationships, b) tailoring strategies to enhance program fit and integration, c) active stakeholder engagement and collaboration, d) capacity building through training, e) accessing new funding, f) adaptation, g) co-creation of intervention and implementation strategies and h) providing infrastructural support. The most prevalent facilitators of sustainability were related to micro-level factors (e.g., intervention fit and community engagement). In contrast, salient barriers were related to structural-level factors (e.g., limited financial resources). Conclusions This review highlights some progress in the published reports on the sustainability of evidence-based intervention in Africa. The review emphasizes the importance of innovation in strategies to foster funding determinants for sustainable interventions. In addition, it underscores the need for developing contextually relevant sustainability frameworks that emphasize these salient determinants of sustainability in the region.